Moderate Intensity Training Impact on the Inflammatory Status and Glycemic Profiles in NOD Mice. (5th August 2015) - Codella, Roberto; Lanzoni, Giacomo; Zoso, Alessia; Caumo, Andrea; Montesano, Anna; Terruzzi, Ileana M.; Ricordi, Camillo; Luzi, Livio; Inverardi, Luca
Abstract : The nonobese diabetic (NOD) mouse represents a well-established experimental model analogous to human type 1 diabetes mellitus (T1D) as it is characterized by progressive autoimmune destruction of pancreatic β -cells. Experiments were designed to investigate the impact of moderate-intensity training on T1D immunomodulation and inflammation. Under a chronic exercise regime, NOD mice were trained on a treadmill for 12 weeks (12 m/min for 30 min, 5 d/wk) while age-matched, control animals were left untrained. Prior to and upon completion of the training period, fed plasma glucose and immunological soluble factors were monitored. Both groups showed deteriorated glycemic profiles throughout the study although trained mice tended to be more compensated than controls after 10 weeks of training. An exercise-induced weight loss was detected in the trained mice with respect to the controls from week 6. After 12 weeks, IL-6 and MIP-1 β were decreased in the trained animals compared to their baseline values and versus controls, although not significantly. Morphometric analysis of pancreata revealed the presence of larger infiltrates along with decreased α -cells areas in the control mice compared to trained mice. Exercise may exert positive immunomodulation of systemic functions with respect to both T1D and inflammation, but only in a stringent therapeutic window.